Hybrid model for the prediction of residual stresses induced by 15-5PH steel turning - Mondelin, Alexandre; Valiorgue, Frédéric; Rech, Joël; Coret, Michel; Feulvarch, Eric (International journal of mechanical sciences, 2012)
This study presents the development of a hybrid model for the prediction of residual stresses induced during the finish turning of a 15-5PH martensitic stainless steel. This new approach consists in replacing tool and chip modeling by equivalent loadings. This model is called “hybrid” because it applies thermomechanical loadings (obtained experimentally) on a numerical model. These equivalent loadings are moved onto the machined surface to compute the final residual stress state. The first part of the present research work proposed to characterize machining equivalent thermo-mechanical loadings at the machined surface level. A new simple method is presented. The case of the dry orthogonal cutting operation of a 15-5PH martensitic stainless steel with coated carbide tools is treated. To this end, two experimental devices and associated numerical models are used. Shapes and locations of equivalent thermo-mechanical loadings are extracted from a Finite Element (FE) simulation of orthogonal cutting. A simplified analytical approach is applied to draw up a list of parameters necessary to calibrate the equivalent loadings. These parameters (friction coefficient, contact length, cutting forces etc.) have to be quantified experimentally. So, tribological tests and orthogonal cutting tests are performed. Finally, using experimental results, machining equivalent thermo-mechanical loadings are quantified. The heat flux, tangential stress and normal pressure at the final workpiece surface are characterized as a function of the cutting speed and the feed. In the second part of this paper, machining equivalent thermo-mechanical loadings previously identified are transferred to a 3D configuration. The objective is to predict the residual stresses induced by a longitudinal finish turning operation on 15-5PH steel. Based on this new approach, the paper also aims at investigating the interactions between each revolution. It is shown that around five revolutions are necessary to reach a steady state for this material. Finally the numerical results are compared with experimental measurements obtained by X-Ray diffraction. It is shown that residual stresses cannot be considered as homogeneous over the surface due to the feed influence. Additionally, the X-Ray beam is too large to quantify this heterogeneity. Based on average numerical values coherent with the average values obtained by X-Ray diffraction, it is shown that the numerical model provides consistent results compared to experimental measurements for a large feed range. ► Hybrid model for the prediction of residual stresses induced by turning. ► Combining of numerical models and experimentations (friction and cutting tests). ► Quantification of the thermal and mechanical impact of the machining process. ► Necessity of a 3D simulation to model a longitudinal turning operation. ► Comparison of numerical and experimental results for a large feed range.